CD4/CD8 ratio is a prognostic factor in IgG nonresponders among peptide vaccine‐treated ovarian cancer patients. Issue 4 (6th March 2020) - Waki, Kayoko; Kawano, Kouichiro; Tsuda, Naotake; Komatsu, Nobukazu; Yamada, Akira
Abstract: The identification of useful biomarkers is an urgent issue in cancer treatment, particularly for immunotherapy, as only some patients experience benefits from this treatment. The early induction of the IgG response has been reported as a useful biomarker of favorable prognosis for cancer patients treated with a personalized peptide vaccination, but a portion of these patients (IgG nonresponders) fail to achieve an early induction of IgG response yet experience long‐term survival. It is thus necessary to identify other biomarkers of favorable prognosis among these patients. Here we report the usefulness of classical T‐cell markers (ie, the CD8 content and the CD4/CD8 ratio in peripheral blood) in IgG nonresponders among advanced or recurrent ovarian cancer patients treated with a personalized peptide vaccination. Among IgG nonresponders (n = 25), the overall survival (OS) of the increased‐CD8 group (n = 7) was significantly longer than that of the decreased‐CD8 group (n = 18; P  = .018), and the OS of the patients with a decreased CD4/CD8 ratio (n = 10) was significantly longer than that of the patients with an increased ratio (n = 15; P  = .0055). Thus, an increased content of CD8 and a decreased CD4/CD8 ratio are each favorable prognosis markers in IgG nonresponders treated with a personalized peptide vaccination. Abstract : Early induction of the IgG response has been reported as a useful biomarker of favorable prognosis for cancer patients treated with a peptide vaccination, but a portion of these patients (IgG nonresponders) fail to achieve an early induction of IgG response yet experience long‐term survival. Here we found the usefulness of classical T‐cell markers (ie, the CD8 content and the CD4/CD8 ratio in peripheral blood) as biomarkers in IgG nonresponders among ovarian cancer patients treated with a personalized peptide vaccination.